PERIOPERATIVE NURSING CARE IN CASES REQUIRING EMERGENCY SURGERY IN COVID-19 INFECTED PATIENTS - Remziye CİCİ (Rojan GÜMÜŞ, 2020)
Covid-19 which emerged in Wuhan, China in December 2019, is an infectious disease caused by coronavirus and causes serious respiratory infections. Covid-19 disease was declared as a pandemic by the World Health Organization in March 2020 due to its easy and rapid spread and affecting many countries globally. This rapid spread also increased the number of individuals infected with the virus, reaching 9,067,559 people worldwide and 187,685 people in Turkey. Unfortunately, deaths resulting from the disease cannot be prevented and the number of individuals who lost their lives continues to increase rapidly. Today, the number of people who died due to the pandemic has reached 500,000 worldwide and 5000 in Turkey. Elective surgery of individuals who are infected or at risk can be postponed in pandemics with such high rate of infectiousness and disease-related mortality. However, if the absence or postponement of the surgery is life-threatening, performing the surgery becomes inevitable. An individual infected or possibly infected with the Covid-19 virus may pose many risks during the surgical procedure, which requires taking some additional precautions before, during and after surgery. In addition to the normal surgical process, perioperative nursing care should focus on some specific issues during the pandemic, which are improving the treatment success of the patients, improving the quality of the care, ensuring that the Covid-19 disease is overcome without complications, and preventing the transmission of the disease to other individuals. Thus, the perioperative nursing care of the Covid-19 patients with possible or definitive diagnosis was discussed considering the available literature.